A Protocol of Process Evaluations of Interventions for the Prevention of Type 2 Diabetes in Women With Gestational Diabetes Mellitus: A Systematic Review. (24th August 2021) - Mohd Sa'id, Iklil Iman; Papachristou Nadal, Iliatha; Forbes, Angus; Goldsmith, Kimberley; Ismail, Irmi Zarina; Hassan, Faezah; Ching, Siew Mooi; Guess, Nicola; Murphy, Helen; Prina, Matthew; Mohd Yusoff, Barakatun Nisak; Basri, Nurul Iftida; et al.
Background: Process evaluations of randomised controlled trials (RCTs) can provide insight and inform us on the intervention implementation, the causal mechanisms and the contextual factors. This will inform about interventions' success or failure due to their implementation or the interventions themselves. We aim to consolidate the methodology from previous process evaluations of complex interventions upon their findings on facilitators and barriers to address the prevention of type 2 diabetes mellitus among women with gestational diabetes mellitus (GDM). Methods: Comprehensive search will be conducted on electronic databases and reference lists of recent reviews for RCTs of complex interventions which address process evaluations of diabetes prevention intervention (DPI) for women with GDM in healthcare settings. There is no restriction on the language of the papers and year of publication until December 2020. Data from each study will be extracted by two reviewers independently using standardised forms. Data extracted include descriptive items on the study design and the outcomes of process evaluations from the three dimensions: (1) implementation; (2) mechanism of impact and (3) context. The quality of the studies will be assessed using mixed methods appraisal tool which is designed for the appraisal of mixed studies in systematic reviews. A narrative and framework analysis of the findings will be presented to inform the contents of a new DPI for women with GDM. Discussion: The findings from this process evaluation findings are valuable in determining whether a complex intervention should be scaled up or modified for other contexts in future plan. It will give deeper understanding of potential challenges and solutions to aid in the implementation of effective DPIs for GDM in Malaysia.